The Incidence of Hyponatraemia and Its Effect on the ECOG Performance Status among Lung Cancer Patients - Amitabha Sengupta; Sourindra Nath Banerjee; Nirendra Mohan Biswas; Debraj Jash; Kaushik Saha; Arnab Maji; Ankan Bandyopadhyaya; Sandip Agarwal (Journal of Clinical and Diagnostic Research, 2013)
Context: Hyponatraemia is one of the common electrolytic disorders which are associated with lung cancer. Hyponatraemia may influence the ECOG performance status at presentation. Also, to the best of our knowledge, we found only limited Indian studies where the ECOG score was correlated with the serum sodium status in lung cancer patients on presentation. Aim: To assess the incidence of hyponatraemia among the patients of carcinoma of the lung before putting them into the specific treatment category for cancer and to check the effects on their ECOG performance status. Settings and Design: A cross–sectional, observational study was conducted on 116 consecutive patients of lung cancer during the period from November 2011 to October 2012. Material and Methods: The patients with a histologically proven diagnosis of lung cancer were grouped initially according to their ECOG performance statuses. The serum sodium value of each patient was measured and the hyponatraemic patients were given treatment according to the protocol. The correlation of the ECOG performance status with the serum sodium of the lung cancer patients was measured. To check for any laboratory error in serum sodium, we selected (n = 58) age, sex and socioeconomic matched control patients. Results: At presentation 44.8% of the lung cancer patients showed hyponatraemia [52/116]. The ECOG score was significantly poor in the advanced clinical stages (ECOG ≤2 Vs ECOG ≥ 3 in NSCLC cases, c2 =11.25, P=.0008). The ECOG performance status score at admission showed a negative correlation with the serum sodium status which was measured on admission among all the patients (Pearson correlation coefficient = – 0.186). The clinical stage of the lung cancer also showed a positive correlation with the ECOG score at admission in our study (Pearson correlation coefficient = 0.295). Conclusion: Hyponatraemia is not an uncommon condition and it should be suspected and screened in each patient, as it may influence the ECOG performance status score, which serves as an important factor in the prognosis of lung cancer.